Kualitas Semen Beku Sapi Bali (Bos sondaicus) Pada Lama Thawing yang Berbeda di Dinas Pertanian Provinsi Gorontalo - Hayati Nur Istiqomah; Muhamad Ervandi; Ishak Korompot; Terri Repi (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to determine the quality of frozen semen of Bali cattle at different thawing times at the Department of Agriculture of the Province of Gorontalo. The observed variables were motility, viability and abnormalities of spermatozoa which were thawed at 30°C for 8, 10 and 12 seconds. The data obtained were analyzed using ANOVA If there are differences of opinion, proceed with testing the Least Significant Difference with the help of SPSS 21 Software. The results showed that a thawing time of 10 resulted in better motility and viability and a lower level of abnormality at 30°C. The thawing time of 10 at a temperature of 30°C can still be used for the purpose of implementing AI in the field because the quality of frozen cement produced by Bali cattle can still be maintained.